Stage Left, Stage Right – The Heavens & Hell: Embodied Meaning & Memory in Performance. (2nd November 2020) - Boyd, Michael
Abstract: Former Artistic Director of the Royal Shakespeare Company Michael Boyd proposes an analogy between the 'thrust' stage and the human brain. On the thrust stage, he suggests, the actor holds the centre of the auditorium, in creative tension with the complex 'mind' of a four‐dimensional space that demands and allows communication with, and between, a thousand different points of view.